Teachers, AI Grammar Checkers, and the Newest Literacies: Emending Writing Pedagogy and Assessment - Jason Toncic (Digital Culture & Education, 2020)
High school English (Language Arts) teachers are experiencing the most impactful shift in literacy practices since the advent of digital word processing: Artificial Intelligence literacies, which impact the production of writing with high-accuracy grammar suggestions. However, the specific role that AI grammar checkers play in teaching and assessing writing has been widely overlooked to date. In this focused study, seven New Jersey (USA) high school English teachers were initially asked about their current writing and grammar pedagogy and assessment. When participants were then introduced to an AI grammar checker, the emergent findings of this study showed that grammar is an implicit factor in student assessment, despite many high school English teachers no longer explicitly teaching grammar lessons. Furthermore, the participating teachers perceived AI grammar checkers as possible “personal assistants” that could improve student writing, teach grammar, and reduce teacher workloads. This study suggests that online grammar checkers can bring about meaningful critical reflection regarding the assessment of Standard English in high schools for teachers and researchers.